Reducing the maximum power consumption of a group of sucker-rod pumps with the mechatronic drive by optimizing the control algorithm - Larin, Mikhail; Volkov, Andrey (E3S web of conferences, 2021)
For the development of lowand medium-rate wells, the most commonly used installations are sucker-rod pumps. The group of sucker-rod pumps connected to the same power supply system is installed on the wells of one oilfield. The work of a sucker-rod pump is cyclical. Obviously, there is a relationship between the maximum power consumption of a group of cycle drives and the performance of this group. Selecting such a strategy for reducing the maximum power consumption, in which there will be no significant performance reduction, is an urgent problem. In this article, theoretical approaches are formulated for constructing the simulation model of a sucker-rod pump group as a group of cycle drives with unequal cycles. Several group control strategies that reduce the maximum value of power consumption are considered.